Questing for Excellence - Akuffo, S.A.B. (My University, 2019)
This lecture gears towards the sensitisation of audience on what goes into the quest for excellence. The lecture begins by defining ‘excellence’ and states that, it is different from what is termed perfection. Further, seven acts of excellence are identified, namely having a defined initiative before beginning a new task; setting priorities to achieve desired results; going the extra mile to achieve excellence in our job description; being ready for the moment by preparing adequately to execute a task; reviewing of past successes and previewing future successes to serve as a motivation to achieving excellence; performing tasks with precision by paying attention to details; and not to allow ourselves to be discouraged by peoples’ negativity. The lecture then touches on five challenges to excellence, namely: resistance to positive change; effective deployment of new technologies as a result of huge investment required to execute tasks; how to strategize to achieve excellence; people’s inefficiency making us look inefficient because they fail to support our goal of achieving excellence; and lack of, or inadequate information hindering ones full potential to be realised. The lecture goes on to encourage the audience to celebrate excellence, and that, when they celebrate excellence, they are invariably telling others that, to do less is to shirk one’s duty to oneself, community and nation. Similarly, in a nation where excellence is rewarded, mediocrity will be shrunk and greatness will beckon. A national commitment to excellence will mean that we all expect the best from each other; that excuses will not do; and everyone will be held to the same high standards. Excellence, according to the lecture is demanded from everybody, and that, the Judicial Service of Ghana has chosen to walk the path of excellence by using ICT tools to deliver expeditious justice. The lecture ends with encouraging the audience, that they can achieve excellence, and that, others have done it. Also, everybody should work towards making Ghana grow to reflect the famous declaration “we are free forever!”
Alumni Lecture
Keywords: resistance; positive change; ffective deployment; technologies